Sweden : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
Sweden's economy has re-gained speed, following supportive macroeconomic policies and strong household demand. Employment has been rising, but the labor force expanded even more, resulting in higher unemployment mostly among vulnerable groups. Inflation remains very low, driven by external and domestic factors. At the same time, financial stability risks are an increasing concern, reflecting high and rising household debt, accelerating house prices, and Sweden's very large banking system.